Macroscopic and Microscopic Morphological Features of Stromatolites Related To Activity of Eukaryote-Dominated Biofilms in an Acid Mine Drainage Environment: Biosignatures and Understanding Preservation of Stromatolites as Trace Fossils. Issue 7 (9th August 2019) - Hasiotis, Stephen T.; Brake, Sandra S.
Abstract: Euglena-, diatom-, and algae-dominated biofilms are the principal producers of iron-rich biolaminates that result in biosedimentary structures, or stromatolites, in an acid mine drainage (AMD) environment in Indiana. These structures are considered trace fossils because they are produced by organism-sediment interactions and record physicochemical conditions of the environment. Our purpose was to link the biofilm types to specific micro- and micromorphological features and the physicochemical conditions under which they were formed. Analyses revealed that Euglena- dominated biofilm produced thin, porous microlaminae by trapping, binding, and relocating AMD precipitates as the biofilm kept pace with chemical sedimentation. More massive microlaminae were produced by high rates of chemical sedimentation brought on by increased discharge and dilution of acidity. Diatom- and algae-dominated biofilms produced thick, mm–cm-scale, porous, spongelike micro- to macrolaminae through oxygenic photosynthesis and/or metal uptake in extracellular polymeric substances, which promoted mineral precipitation on cell walls to create a rigid, porous structure. The variations in biolaminate textures within the stromatolites record seasonal changes in the microbial populations and physicochemical conditions of the AMD environment. These iron-rich stromatolites represent trace fossils that record morphological biosignatures of eukaryote-dominated microbial biofilms and may serve as appropriate proxies in the search for similar evidence of eukaryotic life in other iron-rich paleoenvironments, such as those on early Earth and Mars.